Genetiese bevindings in 'n groep Afrikaners met skisofrenie - Roos, Johannes (AOSIS, 2019)
This book aims to contribute to the understanding of the genetics of schizophrenia. The emphasis is on the collaborative findings of research on this topic done in the Afrikaner founder population from South Africa over more than 20 years. The collaborative research was initiated by the Rockefeller University in New York and the Department of Psychiatry at the University of Pretoria, South Africa. Columbia University, New York, joined the collaboration at a later stage. The genetic laboratory findings elucidate some aspects of the complex nature of the etiopathogenesis of this illness. It further aims to review the clinical findings in this population. A central focus of clinical interest, is early non-psychotic deviant behaviour, prior to the onset of psychosis, in the first 10 years of these patients' lives. It is viewed as an endophenotypic marker in schizophrenia and identifies a subtype of schizophrenia that affects age of onset of illness and long-term prognosis. Clinical research findings may help clinicians to manage these patients, and aid in predicting who is vulnerable to developing the illness. This book also reports on how the scientific findings may be communicated to patients and family members during genetic counselling. There is a constant emphasis on de-stigmatisation of schizophrenia, also among treatment professionals. The original research findings on the genetics of schizophrenia in the Afrikaner founder population over a 20-year period is reviewed and restructured, with emphasis on the clinical and possible etiopathogenic explanations of the illness. The book contributes to scholarship by unfolding genetic laboratory findings and clinical aspects of schizophrenia and how it applies to management.